Sorption-enhanced CO2 methanation to SNG: optimizing conditions in a Ni-Fe/Al2O3 fixed bed reactor - Aragüés, Pablo; Durán, Paúl; Mercader, Víctor; Sanz, Andrés; Francés, Eva; Herguido, Javier; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2022)
This abstract is about the analysis of reaction conditions in which SESaR process to obtain Synthetic Natural Gas (SNG) is carried out. The experiments were done in a fixed bed reactor, with an alumina-supported Ni-Fe catalyst, and the examined parameters were as follows: the ratio [catalyst weight / gas flowrate] (W/Q0), reaction temperatures (both while feeding biogas and when feeding only the reactants CO2 and H2) and, when introducing H2 and CO2, the proportions between these reactants. Moreover, the existence of deactivation, as well as its causes, are proven in long-term experiments.